(untitled) (REMUNOM, 2024)
Considering that accessibility and inclusion are fundamental principles in any psychological practice, and that this applies to the care of deaf individuals, this paper addresses the importance of inclusive psychotherapy for these subjects, highlighting the need for cultural sensitivity on the part of mental health professionals and the importance of using Brazilian Sign Language (Libras) as an effective means of communication. The main objective of this study is to present the significance of Libras in psychological care for deaf individuals from an inclusive perspective. To achieve this goal, a descriptive and qualitative literature review was conducted. The findings of the study reveal the necessity for psychologists to have knowledge of Libras, recognizing and emphasizing that its use plays a crucial role in the effectiveness of psychologists’ work with this population. It not only facilitates communication but also demonstrates a deep commitment to respecting and understanding the culture, identity, and unique experiences of deaf individuals. Therefore, communication in Libras in psychotherapy for the deaf is an essential topic to ensure that everyone has equitable access to psychological services, respecting their linguistic and cultural particularities.